Jakość życia pacjentów z zaćmą = The quality of life of patients with cataracts - Iwona Jaworska; Irena Wrońska (Kazimierz Wielki University, 2015)
Jaworska Iwona, Wrońska Irena. Jakość życia pacjentów z zaćmą = The quality of life of patients with cataracts. Journal of Education, Health and Sport. 2015;5(3):229-246. ISSN 2391-8306. DOI: 10.5281/zenodo.16392 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%283%29%3A229-246 https://pbn.nauka.gov.pl/works/550075 http://dx.doi.org/10.5281/zenodo.16392 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 12.03.2015.   Jakość życia pacjentów z zaćmą   The quality of life of patients with cataracts   Iwona Jaworska, Irena Wrońska   Katedra Rozwoju Pielęgniarstwa. Uniwersytet Medyczny w Lublinie Cathedral of the Development of the Nursing. Medical University in Lublin   Autor do korespondencji Author for the correspondence Iwona Jaworska email: iwonajaworska1@op.pl   Słowa kluczowe: zaćma, jakość życia.   Keywords: cataract, quality of life.   Streszczenie   Cel pracy: Określenie wpływu zmiennych społeczno-demograficznych (płeć, wiek, poziom wykształcenia, stan cywilny) na postrzeganie jakości życia w zaćmie. Materiał i metodyka: Badanie kwestionariuszem Jakości Życia WHOQOL Bref przeprowadzono wśród 300 pacjentów Radomskiego Szpitala Specjalistycznego i Mazowieckiego Szpitala Specjalistycznego w Radomiu Wyniki badań: Analiza wyników wykazała, że chorzy z zaćmą wysoko oceniają jakość swojego życia we wszystkich dziedzinach, jednak najniższej oceny dokonują w zakresie samooceny stanu zdrowia. Stwierdzono też, że płeć, wiek, wykształcenie i stan cywilny korelują z oceną jakości życia. Najniższej oceny jakości życia w dziedzinie somatycznej dokonują kobiety oraz osoby po 75 roku życia. Osoby najstarsze dokonują też niższej niż pozostałe grupy wiekowe oceny stanu zdrowia i jakości życia w dziedzinie fizycznej. Im wyższy poziom wykształcenia chorych z zaćmą tym niższe poczucie jakości życia w dziedzinie fizycznej i niższa ocena stanu zdrowia. Wnioski: W badaniach stwierdzono istnienie istotnej statystycznie zależności pomiędzy badanymi zmiennymi społeczno-demograficznymi (wiek, płeć, poziom wykształcenia, stan cywilny) a samooceną stanu zdrowia, ogólnym poczuciem jakości życia oraz poczuciem jakości życia w dziedzinie fizycznej.   Abstract Aim: To determine the impact of socio-demographic variables (gender, age, education level, marital status), the perception of quality of life in cataract. Material and methods: The study was a questionnaire Quality of Life WHOQOL Bref was conducted among 300 patients Radomski Mazowiecki Specialist Hospital and Specialist Hospital in Radom Test results: Analysis of the results showed that patients with cataract highly appreciate the quality of your life in all areas, but the lowest assessed by self-assessment in the field of health. It was also found that gender, age, education and marital status correlate with the assessment of quality of life. Low quality of life in the field of somatic make women and people over 75 years of age. Oldest person shall also lower than the other age groups assessing the health and quality of life in the physical domain. The higher the level of education of patients with cataract, the lower the quality of life in the physical and lower health assessment. Conclusions: The study found there is no statistically significant correlation between the study of socio-demographic variables (age, gender, education level, marital status) and a self-assessment of health, and the general feeling of quality of life and sense of quality of life in the physical domain.